An audiovisual and interactive recreation of the uncanny: video games and survival horror - Calvo Anoro, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Maturity of video game as a product of popular culture has determined its condition of audiovisual narrative platform. Because of this condition, video game is the latest stage of dramatic writing that offers imaged-based stories in which a key component of its essence is added: interaction. In this way, as a form of storytelling, video game has also reflected about the uncanny, a perspective that Freud stablished in 1919 related to narrative arts. Through the genre of survival horror, video game has created a conceptual space in which the user confronts his fears as the basement of the interactive experience. Basing the analysis on two fundamental works in survival horror —Resident Evil (Shinki Mimaki, 1996) and Silent Hill (Keiichiro Toyama, 1999)—, this article considers how video game has created its particular unheimlich and what have been the aesthetic and interactive contributions that shapes the uncanny from this perspective. The connections with gothic literature or horror cinema joins the immersive capacity of games to stablish an emotional impact in which the user experiments the interactive enjoyment of fear and continues the narrative tradition of horror as a cultural form, but also as a human expression.